Bilingualism in Indonesian Children's Language Acquisition - Aulia Apriana; Adi Sutrisno (Universitas Sanata Dharma, 2022)
Language acquisition and development are two important phases in a child’s life. Hundreds of ideas have been tested to build a scientific explanation for how children may understand and produce the languages of their environment. Language intake, exposure volume and duration, and grammatical complexity all appear to have a role in influencing children's language development. These intricacies become even more complicated as children differ greatly from one another. It's on top of the several languages the children pick up along the route. Some children speak only one language (monolingual), whereas others speak multiple languages (bilingual). Apart from the endless debate about whether being bilingual is a blessing or a curse, it is fascinating to study how those children finally end up being bilinguals, either through acquisition or learning. Therefore, this article aims at portraying the phenomenon of bilingualism in Indonesian children’s language acquisition by looking at the strengths and weaknesses of being bilinguals, the important factors in second language acquisition and learning, and the strategies for second language acquisition and learning. In conclusion, to be bilingual, a child has undergone a very long process. Even though some experts are still debating whether bilingualism is beneficial or even harmful for their cognitive, psychological, and linguistic competence, children nowadays are created to be bilinguals even since they were born. As a result, those children grow up as multilingual children who are ready to cope with the dynamic of the environmental changes around them.